Implications of collective leadership in the implementation of managerial decision-making strategies (Study on people's core plantations Asian Development Bank/ Pir Adb Besitang North Sumatra) - Bangun, Muhammad Fitrah Ashary; Saputra, Andhika Rahmat; Marsudi, Marsudi (Technium Social Sciences Journal, 2021)
The Rahmat Tani Village Unit Cooperative (KUD RATA) carries out the mandate as a forum for an economic organization with a social character to serve the needs of the community by utilizing the consensus results for the strategic achievement of the community itself. Based on its profile, the leadership in this KUD has been proven by its success in delivering the cooperative as one of the national pilot cooperatives. To strengthen the uniqueness of research on the leadership style of KUD RATA, it is necessary to include a description of the decision-making model and the accompanying leadership dynamics for strategic interests while still adhering to the principles of kinship and cooperation. The theory of communicative action from Jurgen Habermas helps us with enlightenment in seeing the deliberative circulation in looking at the systematics of decision making and the dynamics of the KUD RATA leadership style. The results showed that the systematics of decision making at KUD RATA was reflected by the communicative actions of the individuals so that the determination of the direction of cooperative growth in strategic achievement was at the same time adhering to the cooperative principle because its strategic footing remained on the communication paradigm. One of the models of decision-making and leadership style in cooperatives and provides a theoretical contribution to the development of knowledge related to human resource management, especially the systematics of decision-making and the collective leadership style of KUD RATA.